Trace theorems for Sobolev-Slobodeckij spaces with or without weights - Doyoon Kim (Journal of Function Spaces and Applications)
We prove that the well-known trace theorem for weighted Sobolev spaces holds true under minimal regularity assumptions on the domain. Using this result, we prove the existence of a bounded linear right inverse of the trace operator for Sobolev-Slobodeckij spaces Wps(Ω) when s-1/p is an integer.